Identification of Diversity of Coral Fish Species in the Rumpon Area in Banyak Island District, Aceh Singkil Regency - Hamzanul Arif; Burhanis Burhanis (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2023)
This study aims to determine the diversity and abundance of reef fish around FADs in Balai Island Waters. This research was conducted in October - December 2022 in the waters of Balai Island, Aceh Singkil Regency. The method used is a Stationary Visual Census then identified using the reef fish identification guidebook. Based on the results of the study, 9 species of reef fish were identified, consisting of 6 species. The abundance of reef fish is 1.3 is included in the medium category, the diversity index is 1.676 medium category, uniformity is 0.935 abundance category, and dominance is 0.209 low category